Cracking the diagnostic puzzle of tumours of adrenal cortex: a histopathological study - Madabhushi, Venugopal; Chaganti, Padmavathi Devi; Katta, Ramya; Kakumanu, Nageswararao (International Journal of Research in Medical Sciences, 2016)
Background: Primary neoplasms arising in both adrenal cortex and adrenal medulla are rare tumors. Adrenal cortical tumours may be functional or non-functional. They may be found incidentally at the time of autopsy. In many cases adrenal lesions are identified during a radiologic investigation conducted for indications other than an evaluation for adrenal disease. Adrenocortical tumours can be categorized into adenomas and carcinomas, but the distinction becomes difficult in many cases. Several parameters have been applied to establish malignancy in these tumours. Histopathology is still the gold standard in diagnosis of adrenal tumours. This is a retrospective study and was to study the incidence of tumours of adrenal cortex and to assess the role of histopathological criteria and utility of immunohistochemistry in the diagnosis. Methods: Adrenal cortical tumors reported from August, 2008 to August, 2015 in the Department of Pathology, Guntur Medical College, Andhra Pradesh, India are taken for the study. Clinical data including age, sex and symptoms at presentation, are retrieved from the archives. The resected specimens received from Government General Hospital, Guntur, Andhra Pradesh, India are routinely processed and multiple sections stained with Haematoxylin & Eosin are examined. Modified Weiss criteria are applied for all adrenal cortical tumors in the study. Immunohistochemistry is done in relevant cases for confirmation of diagnosis. Results: The observations in the study including clinical presentation, gross and histological features are tabulated. Conclusions: The study highlights the crucial role of histopathological parameters, especially Weiss criteria in identifying malignancy in tumours of adrenal cortex and importance of immunohistochemistry in differential diagnosis.